2007
DOI: 10.1182/blood-2006-10-048173
|View full text |Cite
|
Sign up to set email alerts
|

The unexpected effect of cyclosporin A on CD56+CD16− and CD56+CD16+ natural killer cell subpopulations

Abstract: Cyclosporin A (CSA) is commonly used to prevent graft-versus-host disease. The influence of CSA on T-cell function has been extensively investigated; however, the effect of CSA on natural killer (NK) cells is less understood. NK cells were cultured with IL-2 and IL-15 with and without CSA for 1 week. Compared with controls, CSA-treated cultures showed fewer CD56+CD16+KIR+ NK cells and a reciprocal increase in CD56+CD16−KIR− cells. These changes were due mainly to a reduced proliferation of the CD56dim NK-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
77
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 63 publications
12
77
0
1
Order By: Relevance
“…Thus, as CD56 bright NK cells were still abundantly present in the CsA-treated cultures, in contrast to MPA-and Rapa-treated cultures, the IFN- production upon cytokine stimulation may largely be preserved after CsA treatment. This was confirmed in a study showing sustained IFN- production by CsA-treated NK cell cultures upon IL-12 and IL-18 stimulation (Wang et al, 2007), suggesting that IFN--mediated GVL reactivity after allogeneic SCT should remain intact when using CsA as GVHD prophylaxis. Our findings on the effect of CsA and MPA on the cytolytic response by in vitro cytokinestimulated NK cells are in concert with previous findings on this subject (Ohata et al, 2011).…”
Section: Interference By Immunosuppressive Drugssupporting
confidence: 57%
“…Thus, as CD56 bright NK cells were still abundantly present in the CsA-treated cultures, in contrast to MPA-and Rapa-treated cultures, the IFN- production upon cytokine stimulation may largely be preserved after CsA treatment. This was confirmed in a study showing sustained IFN- production by CsA-treated NK cell cultures upon IL-12 and IL-18 stimulation (Wang et al, 2007), suggesting that IFN--mediated GVL reactivity after allogeneic SCT should remain intact when using CsA as GVHD prophylaxis. Our findings on the effect of CsA and MPA on the cytolytic response by in vitro cytokinestimulated NK cells are in concert with previous findings on this subject (Ohata et al, 2011).…”
Section: Interference By Immunosuppressive Drugssupporting
confidence: 57%
“…Following receptor ligation free intracellular Ca 2ϩ increases, triggering a series of downstream events including the activation of calcineurin. It has been recently shown that CsA-treated NK cells exhibit an alteration of calcineurin activity that disrupts intracellular Ca 2ϩ patterns and blocks NFAT translocation (67). What effects this has on later stages of NK cell activation are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CsA pharmacodynamic effect on NK cells is distinct and allows NK cell cytotoxicity, 41 whereas it is impaired by MMF [42][43][44] or MTX. [45][46][47] Moreover, calcineurin inhibitors are the only immunosuppressive agents exerting their action by inhibiting interleukin-2 production.…”
Section: Discussionmentioning
confidence: 99%